2021
DOI: 10.1051/0004-6361/202039709
|View full text |Cite
|
Sign up to set email alerts
|

GaiaEarly Data Release 3

Abstract: Context. Gaia Early Data Release 3 (Gaia EDR3) contains results for 1.812 billion sources in the magnitude range G = 3–21 based on observations collected by the European Space Agency Gaia satellite during the first 34 months of its operational phase. Aims. We describe the input data, the models, and the processing used for the astrometric content of Gaia EDR3, as well as the validation of these results performed within the astrometry task. Methods. The processing broadly followed the same procedures as for Gai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
437
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 899 publications
(448 citation statements)
references
References 41 publications
10
437
1
Order By: Relevance
“…The stellar mass errors contribute 7%, 67%, 36%, 5%, 82%, 95%, 27%, and 84% to the uncertainty of the masses of HD 131664 B, HD 16160 C, HD 161797 Ab, HD 190360 b, HD 190406 B, HD 39587 B, HD 4747 B, and HIP 2552 C, respectively. Second, because the five-parameter astrometry model used in Gaia EDR3 (Lindegren et al 2021) does not account for companion-induced nonlinear motion of a star, the longer baseline of Gaia EDR3 does not improve the fit much for stars with massive companions. In particular, the Gaia EDR3 astrometry is more uncertain than the DR2 astrometry for HD 131664, HD 16160, and HIP 2552.…”
Section: Comparison Of Orbital Solutionsmentioning
confidence: 99%
“…The stellar mass errors contribute 7%, 67%, 36%, 5%, 82%, 95%, 27%, and 84% to the uncertainty of the masses of HD 131664 B, HD 16160 C, HD 161797 Ab, HD 190360 b, HD 190406 B, HD 39587 B, HD 4747 B, and HIP 2552 C, respectively. Second, because the five-parameter astrometry model used in Gaia EDR3 (Lindegren et al 2021) does not account for companion-induced nonlinear motion of a star, the longer baseline of Gaia EDR3 does not improve the fit much for stars with massive companions. In particular, the Gaia EDR3 astrometry is more uncertain than the DR2 astrometry for HD 131664, HD 16160, and HIP 2552.…”
Section: Comparison Of Orbital Solutionsmentioning
confidence: 99%
“…Consequently, the high observed ejection velocities of disk runaways call for an as yet mostly neglected mechanism possibly involving very massive stars (Gvaramadze 2009;Gvaramadze et al 2009) or intermediate-mass black holes (Fragione & Gualandris 2019), see Irrgang et al (2018a) for a more detailed discussion. With proper motions of significantly improved accuracy and precision from the Gaia early data release 3 (EDR3, Gaia Collaboration 2021; Lindegren et al 2021), it is now possible to determine whether this trend continues.…”
Section: Introductionmentioning
confidence: 99%
“…The EDR3 Gaia parallaxes (Lindegren et al 2021) were used to calculate the distances and absolute magnitudes shown in Tables 1 and 2. Paper I, which used the DR2 Gaia parallaxes, showed that the majority of CVs from ZTF had absolute magnitudes at quiescence between 10 and 12, near the faint end of previous results in the literature (Warner 1987(Warner , 1995.…”
Section: Absolute Magnitudesmentioning
confidence: 99%